Organic covalent cross-linked alginic acid fiber as well as preparation method and application thereof
Alginic acid fibers prepared through organic covalent cross-linking technology solve the problem of insufficient adsorption sites and adsorption capacity of existing alginic acid adsorption materials, and achieve efficient heavy metal recovery, water softening and organic pollutant removal.
Patent Information
- Application Number
- CN202411477284.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing alginic acid adsorbent materials improve water resistance through Ca2+ ion crosslinking technology, but sacrifice the adsorption site and adsorption amount, limiting their promotion and application in the field of water treatment.
Alginate fiber is prepared using organic covalent cross-linking technology. Water-insoluble alginate fiber is prepared by cross-linking the alginate fiber in an acidic aqueous solution or organic solution of an organic covalent cross-linking agent.
The adsorption capacity and adsorption performance of the alginic acid adsorption material are improved, and it can effectively recover or remove heavy metals in aqueous solutions, soften drinking water, and remove cationic organic pollutants. It has the characteristics of fast adsorption rate and easy solid-liquid separation.
Smart Images

Figure CN119352193A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of valuable metal recovery and water purification, and more specifically, relates to an organic covalently cross-linked alginate fiber, a preparation method and application thereof. Background Art
[0002] Alginate has attracted extensive attention for its wide sources, low cost, and environmental friendliness in the recovery of valuable resources and removal of pollutants in aqueous solutions. However, the water-soluble properties of alginate greatly limit its application in water environments. Therefore, how to improve the water resistance of alginate-based materials has great research value in broadening the application of alginate-based materials in the field of water treatment.
[0003] At present, the water solubility of alginate is mainly overcome by combining alginate molecules with calcium ions (Ca 2+ ) to improve the water resistance of alginate-based materials (such as Figure 1 However, Ca 2+ The introduction of ions will form competitive adsorption with cationic pollutants, greatly reducing the recovery of cationic valuable metals and the removal performance of cationic pollutants by alginate-based adsorption materials. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide an organic covalently cross-linked alginate fiber, a preparation method thereof, and an application in the field of resource recovery and water treatment agent technology in aqueous solution to solve the problem of Ca 2+ The alginate adsorption material prepared by ionic cross-linking technology sacrifices adsorption sites and has small adsorption capacity, which are technical problems that limit its popularization and application.
[0005] To achieve the above object, the present invention provides a method for preparing organic covalently cross-linked alginate fibers, comprising the following steps:
[0006] (1) mixing sodium alginate and water to obtain alginate hydrogel;
[0007] (2) extruding the alginate hydrogel in step (1) into an acidic aqueous solution or an organic solution to form fibers in the solution, and performing solid-liquid separation to obtain alginate fibers; wherein the alginate fibers are insoluble in the acidic aqueous solution or the organic solution;
[0008] (3) drying the alginate fibers in step (2) and immersing them in an acidic aqueous solution or an organic solution of an organic covalent crosslinking agent to cause an organic covalent crosslinking reaction, and after the reaction, washing and drying the fibers to obtain organic covalently crosslinked alginate fibers; and the alginate fibers are insoluble in the acidic aqueous solution or the organic solution of the organic covalent crosslinking agent;
[0009] Wherein, the acidic aqueous solutions in step (2) and step (3) are the same or different, and the organic solutions in step (2) and step (3) are the same or different.
[0010] Preferably, in step (1), the sodium alginate and water are mixed, and the mass ratio of the sodium alginate to water is (2-6):100.
[0011] Preferably, the acidic aqueous solutions in step (2) and step (3) are each independently one or more acidic aqueous solutions having a pH value less than 2;
[0012] The organic solutions in step (2) and step (3) are independently one or more of methanol, ethanol, and N,N-dimethylformamide.
[0013] Preferably, the organic covalent crosslinking agent in step (3) is one or more of epichlorohydrin, ethylene glycol diglycidyl ether and glutaraldehyde.
[0014] Preferably, the volume percentage concentration of the organic covalent crosslinking agent in the acidic aqueous solution or organic solution of the organic covalent crosslinking agent is 0.5-25%, and more preferably 0.5-10%.
[0015] Preferably, the reaction temperature during the organic covalent cross-linking reaction is 70-100° C., and the reaction time is 6-12 h.
[0016] Preferably, in step (3), the ratio of the alginate fiber to the acidic aqueous solution or organic solution of the organic covalent cross-linking agent is 1 g: 50-200 mL.
[0017] According to another aspect of the present invention, there is provided an organic covalently cross-linked alginate fiber prepared by the preparation method.
[0018] According to another aspect of the present invention, there is provided a use of the organic covalently cross-linked alginate fibers in the adsorption removal or recovery of heavy metals in aqueous solutions, or in softening drinking water.
[0019] According to another aspect of the present invention, there is provided a use of the organic covalently cross-linked alginate fibers in removing cationic organic pollutants in aqueous solution.
[0020] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0021] The present invention provides an organic covalently cross-linked alginate fiber, which is prepared by immersing the alginate fiber in an acidic aqueous solution of an organic covalent cross-linking agent or an organic solution of an organic covalent cross-linking agent in which alginate is insoluble to produce an organic covalent cross-linking reaction. When applied to the technical fields of resource recovery in aqueous solution and water treatment agent, it can solve the problem of Ca in existing alginate. 2+ The alginate adsorption material prepared by ionic crosslinking technology sacrifices adsorption sites, resulting in a small adsorption amount and other technical problems that limit its promotion and application. The preparation conditions of this method are simple and mild. The prepared organic covalently crosslinked alginate fibers can be used for the recovery / removal of heavy metals in aqueous solutions, the softening of drinking water, and the removal of cationic organic pollutants in aqueous solutions. It has the characteristics of fast adsorption rate, high adsorption performance, and easy solid-liquid separation. In addition, the organic covalently crosslinked alginate fibers can be regenerated and reused. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic diagram of the synthesis mechanism of water-resistant alginate using traditional calcium ion electrostatic cross-linking;
[0023] Figure 2 It is a schematic diagram of the process of preparing the organic covalently cross-linked alginate fiber of the present invention;
[0024] Figure 3 This is an evaluation of the adsorption performance of Sn(II) in an acidic aqueous solution by organic covalently cross-linked alginate fibers prepared with different cross-linking agent concentrations in Example 3 (adsorption conditions: pH≈1, adsorbent dosage=0.5 g / L);
[0025] Figure 4 It is an evaluation of the adsorption performance of organic covalently cross-linked alginate fibers for Pb(II), Cd(II), and Zn(II) provided in an embodiment of the present invention (adsorption conditions: pH≈5, adsorbent dosage=0.5 g / L);
[0026] Figure 5 The present invention provides a study on the regeneration performance of organic covalently cross-linked alginate fibers;
[0027] Figure 6 It is an evaluation of the adsorption performance of organic covalently cross-linked alginate fibers for Ca(II) and Mg(II) provided in an embodiment of the present invention (adsorption conditions: pH≈7, adsorbent dosage=0.5 g / L);
[0028] Figure 7 These are digital photos of the organic covalently cross-linked alginate fibers provided in an embodiment of the present invention before and after the adsorption of methylene blue (adsorption conditions: pH≈7, adsorbent dosage=0.4 g / L). DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described in conjunction with the accompanying drawings and embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0030] The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0031] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0032] The process parameters without specific conditions in the following examples are usually based on conventional conditions.
[0033] The present invention provides a method for preparing organic covalently cross-linked alginate fibers, such as Figure 2 As shown, the following steps are included:
[0034] (1) mixing sodium alginate and water to obtain alginate hydrogel;
[0035] (2) The alginate hydrogel of step (1) is squeezed into an acidic aqueous solution or an organic solution to form alginate fibers in the solution, and the alginate fibers are obtained by solid-liquid separation; and the alginate fibers are insoluble in the acidic aqueous solution or the organic solution; the solid-liquid separation here can be directly fished out, or other conventional solid-liquid separation methods can be used to remove the solution portion.
[0036] (3) drying the alginate fibers in step (2) and immersing them in an acidic aqueous solution or an organic solution of an organic covalent crosslinking agent to cause an organic covalent crosslinking reaction, and after the reaction, washing and drying the fibers to obtain organic covalently crosslinked alginate fibers; the alginate fibers are insoluble in the acidic aqueous solution or the organic solution of the organic covalent crosslinking agent; wherein the acidic aqueous solutions in step (2) and step (3) may be the same or different; and the organic solutions in step (2) and step (3) may be the same or different.
[0037] The "insoluble" mentioned in the present invention means that the alginate fibers still maintain a good fiber morphology in the acidic aqueous solution or organic solution.
[0038] In some embodiments, in step (1), the sodium alginate and water are mixed, and the mass ratio of the sodium alginate to water is (2-6): 100. The acidic aqueous solution in step (2) and step (3) is independently one or more acidic aqueous solutions with a pH value less than 2, including but not limited to aqueous solutions with a pH value less than 2 such as hydrochloric acid, sulfuric acid, and nitric acid; the organic solution in step (2) and step (3) is independently one or more liquid organic solvents such as methanol, ethanol, and N,N-dimethylformamide.
[0039] In some embodiments, the alginate hydrogel in step (2) is squeezed into an acidic aqueous solution or an organic solution, and alginate fibers can be obtained by squeezing the alginate gel into the acidic aqueous solution or the organic solution by compressed air squeezing or mechanical squeezing.
[0040] In some embodiments, the organic covalent crosslinking agent in step (3) is one or more of epichlorohydrin (ECH), ethylene glycol diglycidyl ether (EGDE) and glutaraldehyde (GA), preferably ECH.
[0041] In some embodiments, the volume percentage concentration of the organic covalent crosslinking agent in the acidic aqueous solution or organic solution of the organic covalent crosslinking agent is 0.5-25%, preferably 0.5-10%, and more preferably 0.5-8%. The reaction temperature during the organic covalent crosslinking reaction is 70-100°C, and the reaction time is 6-12h. In step (3), the amount ratio of the alginate fiber to the acidic aqueous solution or organic solution of the organic covalent crosslinking agent is 1g:50-200mL.
[0042] The alginate fiber prepared by the preparation method of the present invention has been experimentally confirmed to be used for adsorption removal or recovery of heavy metals in aqueous solution, or softening drinking water, where the aqueous solution can be various wastewaters (including but not limited to simulated steel cold rolling wastewater, electroplating wastewater, etc.). In some embodiments, the alginate fiber after adsorbing heavy metals or softening drinking water can be regenerated by acidic aqueous solution such as nitric acid and hydrochloric acid and then reused.
[0043] The alginate fiber prepared by the preparation method of the present invention can also be used to remove cationic organic pollutants in aqueous solution through experiments. In some embodiments, the cationic organic pollutants are one or more of methyl blue, crystal violet, malachite green, etc.
[0044] The present invention uses non-ionic crosslinking, i.e., organic covalent crosslinking technology to prepare alginate fibers with good water resistance, which are used for the recovery / removal of heavy metals in aqueous solutions, the softening of drinking water, and the removal of cationic organic pollutants. Experiments have shown that compared with the prior art calcium ion crosslinked alginate fibers, the organic covalent crosslinked alginate fibers of the present invention can greatly increase the adsorption capacity of alginate adsorbent materials.
[0045] The following are examples:
[0046] Example 1
[0047] A method for preparing organic covalently cross-linked alginate fibers comprises the following steps:
[0048] (1) 3.75 g of sodium alginate and 96.25 g of water were mixed and stirred to obtain an alginate hydrogel;
[0049] (2) The alginate hydrogel of step (1) is squeezed into an anhydrous ethanol solution at a pressure of 0.2-0.4 MPa through an air compressor to obtain alginate fibers, which are then removed and freeze-dried;
[0050] (3) 0.05 g of the alginate fiber prepared in step (2) was immersed in 10 mL of an ECH N,N-dimethylformamide solution, where the ECH concentration was 1% (v / v), and an organic covalent crosslinking reaction was carried out at 80° C. for 12 h, and then the alginate fiber was washed with deionized water and dried to obtain an organic covalently crosslinked alginate fiber. The ratio of the alginate fiber to the ECH N,N-dimethylformamide solution was 1 g: 200 mL.
[0051] The other steps were the same as those in Example 1, and the preparation conditions were changed to obtain the organic covalently cross-linked alginate fibers of Examples 2 to 13. The preparation conditions and the water solubility of the alginate fibers are listed in Table 1.
[0052] Table 1. Stability of organic covalently cross-linked alginate fibers in water prepared under different conditions
[0053]
[0054]
[0055] It can be seen from Table 1 that the organic covalently cross-linked alginate fibers prepared under the conditions of each embodiment have good water resistance.
[0056] Comparative Example 1
[0057] The uncrosslinked alginate fibers obtained in step (2) of Example 1 were dried and a small amount was mixed with water. It was found that the alginate fibers dissolved in water.
[0058] Comparative Example 2
[0059] The other steps are the same as those in Example 1, except that the concentration of the organic covalent crosslinking agent in step (3) is replaced with 0% to obtain alginate fibers. After drying, a small amount is mixed with water and found to be soluble in water. This indicates that in the synthesis process of the alginate fibers with good water resistance prepared in Examples 1-13, the crosslinking agents (ECH, EGDE, GA) play a major role, and the solvent used (N,N-dimethylformamide, pH=1 hydrochloric acid aqueous solution) does not participate in the reaction.
[0060] Comparative Example 3
[0061] The other steps are the same as those in Example 1, except that the concentration of the organic covalent crosslinking agent in step (3) is replaced with 8%, 10%, 15%, and 20%, respectively, and organic covalently crosslinked alginate fibers are obtained respectively.
[0062] The alginate fibers cross-linked with different organic covalent cross-linking agent concentrations were used to recover Sn(II) from acidic steel cold rolling simulated wastewater. The initial concentration of Sn(II) was about 800 mg / L, the dosage of organic covalent cross-linked alginate fibers was 0.5 g / L, the adsorption pH was 1, the temperature was 25°C, and the adsorption time was 3 h. The experiment measured that when the ECH concentration of organic covalent cross-linked alginate fibers increased from 8% to 20% during the preparation process, its adsorption capacity for Sn(II) decreased from 341.1 mg / g to 7.8 mg / g (see Figure 3 ). This may be because during the material preparation process, the high concentration of the cross-linking agent will consume a large number of adsorption sites (carboxyl, -COOH), thus significantly reducing its adsorption capacity for Sn(II).
[0063] Embodiment 14
[0064] The covalently cross-linked alginate fibers prepared in Example 1, Example 4, Example 5 and Example 6 were used to adsorb Pb(II), Cd(II) and Zn(II) in simulated aqueous solutions. The initial concentration of Pb(II), Cd(II) or Zn(II) was 200 mg / L, the dosage of organic covalently cross-linked alginate fibers was 0.5 g / L, the adsorption pH was 5, the temperature was 25°C and the adsorption time was 3 hours. The experimental results show that the adsorption amounts of Pb(II), Cd(II) and Zn(II) were 313.3-348.9 mg / g, 217.2-240.2 mg / g and 122.9-149.0 mg / g, respectively (see Figure 4 ), which is higher than most of the adsorbents reported so far (Table 2).
[0065] In addition, the heavy metal-loaded organic covalently cross-linked alginate fibers obtained after adsorption in Example 14 were separated from the aqueous solution and then immersed in a 1M HNO3, HCl acidic solution for regeneration of the adsorbent. The desorption time was 1 hour. The regenerated adsorbent was rinsed with deionized water until neutral. The adsorption performance of the regenerated adsorbent for metal ions was further evaluated according to the above adsorption conditions. Figure 5 As shown in the figure, after three adsorption-desorption cycles, the adsorption performance of heavy metal ions did not decrease significantly. This further indicates that heavy metal-loaded organic covalently cross-linked alginate fibers can be completely regenerated with acidic solutions such as HNO3 and HCl.
[0066] Table 2. Comparison of adsorption performance of biomass adsorption materials for Zn(II), Cd(II) and Pb(II)
[0067]
[0068] Embodiment 15
[0069] The organic covalently cross-linked alginate fibers prepared in Examples 1, 4, 5 and 6 were used to remove Ca(II) and Mg(II) ions in a neutral (pH≈7) simulated aqueous solution. The initial concentration of Ca(II) and Mg(II) ions was about 200 mg / L, the dosage of organic covalently cross-linked alginate fibers was 0.5 g / L, the temperature was 25°C, and the adsorption time was 3 hours. The relevant results are shown in Figure 6 The results show that the prepared adsorbent material can be effectively used for the removal of Ca(II) and Mg(II) ions in a neutral (pH≈7) environment, indicating that the prepared organic covalently cross-linked alginate fibers can be used for water softening.
[0070] Example 16
[0071] The adsorption performance of the organic covalently cross-linked alginate fiber prepared in Example 2 for the cationic dye methylene blue is shown in Figure 7 As shown, organic covalently cross-linked alginate fibers have a significant removal effect on methylene blue in the solution. The color of the methylene blue solution is significantly reduced after adsorption. Under the conditions of initial concentrations of 10 mg / L and 100 mg / L, solution pH ≈ 7, and adsorbent dosage = 0.4 g / L, the removal rate of methylene blue is higher than 95%.
[0072] References:
[0073] [1]M.Kaur,S.Kumari,P.Sharma,Response surface methodology adheringcentral composite design for the optimization of Zn(II)adsorption using ricehusk nanoadsorbent,Chemical Physics Letters,801(2022).
[0074] [2]X.Yang,F.Zhao,Adsorption thermodynamics and kinetics ofhydrochloric-acid-modified bentonite for Zn(II)in wastewater,Desalination andWater Treatment,317(2024).
[0075] [3]M.Amin,P.Chetpattananondh,Biochar from extracted marine Chlorellasp.residue for high efficiency adsorption with ultrasonication to remove Cr(VI),Zn(II)and Ni(II),Bioresour Technol,289(2019)121578.
[0076] [4]D.Zhao,H.Wang,Z.Wang,S.Lu,Understanding competitive Cu(2+)and Zn(2+)adsorption onto functionalized cellulose fiber via experimental andtheoretical approach,Int J Biol Macromol,273(2024)132782.
[0077] [5]H.Wang,J.M.H.Al-Kurdhani,J.Ma,Y.Wang,Adsorption of Zn2+ion bymacadamia nut shell biochar modified with carboxymethyl chitosan andpotassium ferrate,Journal of Environmental Chemical Engineering,11(2023).
[0078] [6]S.S.Salih,T.K.Ghosh,Adsorption of Zn(II)ions by chitosancoateddiatomaceous earth,Int J Biol Macromol,106(2018)602-610.
[0079] [7]E.Khanniri,M.Yousefi,A.M.Mortazavian,N.Khorshidian,S.Sohrabvandi,M.R.Koushki,S.Esmaeili,Biosorption of cadmium from aqueoussolution bycombination of microorganisms and chitosan:response surfacemethodology foroptimization of removal conditions,Journal of EnvironmentalScience andHealth,Part A,58(2023)433-446.
[0080] [8]Z.Yu,Q.Dang,C.Liu,D.Cha,H.Zhang,W.Zhu,Q.Zhang,B.Fan,Preparationand characterization of poly(maleic acid)-grafted cross-linkedchitosanmicrospheres for Cd(II)adsorption,Carbohydrate Polymers,172(2017)28-39.
[0081] [9]E.M.Saad,R.F.Elshaarawy,S.A.Mahmoud,K.M.El-Moselhy,NewUlva lactucaAlgae Based Chitosan Bio-composites for Bioremediation of Cd(II)Ions,Journalof Bioresources and Bioproducts,6(2021)223-242.
[0082]
[10] S.Begum,N.Y.Yuhana,N.M.Saleh,Z.Shaikh,Synthesis andapplication offatty acid-modified chitosan for heavy metal remediation fromwaste water,Carbohydrate Polymer Technologies and Applications,7(2024).
[0083]
[11] M.A.A.Aljar,S.Rashdan,A.Almutawah,A.A.El-Fattah,SynthesisandCharacterization of Biodegradable Poly(vinyl alcohol)-Chitosan / CelluloseHydrogel Beads for Efficient Removal of Pb(II),Cd(II),Zn(II),and Co(II)fromWater,Gels,9(2023).
[0084]
[12] W.Wang,Q.Lu,Z.Zhuo,W.Zhang,H.Liu,J.Zhang,J.Zhou,Y.Niu,T.Guerrero,Synthesis and characterization of recyclable O-carboxymethylchitosan Schiffbase for the effective removal of Cd(II)from aqueous solution,Desalinationand Water Treatment,189(2020)264-275.
[0085]
[13] F.Zhao,E.Repo,D.Yin,M.E.T. Adsorption of Cd(II)andPb(II)by a novel EGTA-modified chitosan material:Kinetics and isotherms,Journal ofColloid and Interface Science,409(2013)174-182.
[0086]
[14] E.Lopez,M.Gómez,I.Becar,P.Zapata,J.Pizarro,M.Navlani-García,D.Cazorla-Amorós,V.Presser,T.Gómez,C.Cárdenas,Removal of Mo(VI),Pb(II),and Cu(II)from wastewater using electrospuncellulose acetate / chitosan biopolymerfibers,International Journal of BiologicalMacromolecules,269(2024).
[0087]
[15] M.B.Yahia,R.Gerhardt,L.Sellaoui,H.Y.S.Al-Zahrani,A.P.O.Inácio,D.Dias,T.R.S.A.Cadaval,L.A.de Almeida Pinto,A.Bonilla-Petriciolet,M.Badawi,Anemerging application of chitosan and chitosan / spirulina films forPb2+adsorption:New physicochemical insights via experimental andtheoreticalstudies,Separation and Purification Technology,337(2024).
[0088]
[16] H.Majiya,F.Clegg,C.Sammon,Bentonite-Chitosan composites orbeadsfor lead(Pb)adsorption:Design,preparation,and characterisation,Applied ClayScience,246(2023).
[0089]
[17] X.Liu,Y.Zhang,Y.Liu,T.a.Zhang,Preparation ofpolyamidoaminedendrimer-functionalized chitosan beads for the removal of Ag(I),Cu(II),andPb(II),International Journal of Biological Macromolecules,242(2023).
[0090]
[18] W.Wang,L.Qi,S.Han,H.Yuan,Synthesis,characterization ofchitosan-trithiocyanuric and its removal mechanism of Cr(VI)and Pb(II)fromwastewater,Chemical Engineering Science,281(2023).
[0091]
[19] L.Xiao,H.Shan,Y.Wu,Chitosan cross-linked and graftedwithepichlorohydrin and 2,4-dichlorobenzaldehyde as an efficient adsorbentforremoval of Pb(II)ions from aqueous solution,International JournalofBiological Macromolecules,247(2023).
[0092]
[20] Y.Chen, J.Tang, S.Wang, L.Zhang, Ninhydrin-functionalizedchitosan for selective removal of Pb(II)ions: Characterization and adsorption performance, International Journal of Biological Macromolecules, 177 (2021) 29-39.
[0093]
[21] X.Liu, Y.Wang,
[0094] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing organic covalently cross-linked alginate fibers, characterized in that: The steps include: (1) mixing sodium alginate and water to obtain alginate hydrogel; (2) extruding the alginate hydrogel in step (1) into an acidic aqueous solution or an organic solution to form fibers in the solution, and performing solid-liquid separation to obtain alginate fibers; wherein the alginate fibers are insoluble in the acidic aqueous solution or the organic solution; (3) drying the alginate fibers in step (2) and immersing them in an acidic aqueous solution or an organic solution of an organic covalent crosslinking agent to cause an organic covalent crosslinking reaction, and washing and drying the fibers after the reaction to obtain organic covalently crosslinked alginate fibers; wherein the alginate fibers are insoluble in the acidic aqueous solution or the organic solution of the organic covalent crosslinking agent; Wherein, the acidic aqueous solutions in step (2) and step (3) are the same or different; and the organic solutions in step (2) and step (3) are the same or different.
2. The preparation method according to claim 1, characterized in that Step (1) Mixing the sodium alginate and water, wherein the mass ratio of the sodium alginate to water is (2-6):
100.
3. The preparation method according to claim 1, characterized in that: The acidic aqueous solutions in step (2) and step (3) are each independently one or more acidic aqueous solutions having a pH value less than 2; The organic solutions in step (2) and step (3) are independently one or more of methanol, ethanol, and N,N-dimethylformamide.
4. The preparation method according to claim 1, characterized in that: The organic covalent crosslinking agent in step (3) is one or more of epichlorohydrin, ethylene glycol diglycidyl ether and glutaraldehyde.
5. The preparation method according to claim 1, characterized in that: The volume percentage concentration of the organic covalent crosslinking agent in the acidic aqueous solution or organic solution of the organic covalent crosslinking agent is 0.5-25%.
6. The preparation method according to claim 1, characterized in that: The reaction temperature during the organic covalent cross-linking reaction is 70-100° C. and the reaction time is 6-12 hours.
7. The preparation method according to claim 1, characterized in that: In step (3), the ratio of the alginate fiber to the acidic aqueous solution or organic solution of the organic covalent cross-linking agent is 1 g: 50-200 mL.
8. Organic covalently cross-linked alginate fibers prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the organic covalently cross-linked alginate fibers as claimed in claim 8 in the adsorption removal or recovery of heavy metals in aqueous solutions, or in the softening of drinking water.
10. Use of the organic covalently cross-linked alginate fibers as claimed in claim 8 in removing cationic organic pollutants in aqueous solution.
Citation Information
Patent Citations
Absorbable antibacterial alginate fibers
CN104631118A
Electrostatic spinning continuous production method for sodium alginate nano fibers
CN106245159A
Chemically cross-linked modified alginate fiber and preparation method thereof
CN106435833A
Fibrous adsorbent of alginic acid, production method of fibrous adsorbent of alginic acid, and adsorption method using fibrous adsorbent
JP2017042689A
A preparation method of alginate microfibers
KR1020130009483A